2017
DOI: 10.1016/j.joen.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Apical Periodontitis on Stress Oxidative Parameters in Diabetic Rats

Abstract: Our findings indicate that diabetes may change the antioxidant status, increase the concentration of MDA and uric acid, and decrease albumin levels in the serum. In addition, AP can potentiate the effects of diabetes by reducing the levels of albumin and increasing the levels of uric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Consequently, lesions in the periapical area were larger in diabetic rats compared to those in the control group. 26 Subsequently, other animal studies 6,[27][28][29][30][31] comparing the severity of inflammation and periapical bone loss between patients with diabetes and normoglycemic controls were conducted and are in agreement with the findings obtained by Kohsaka et al 26 In addition, one of these studies showed that diabetes may enhance the production of IL-17 in the AP site of rats, 31 confirming that diabetes may influence the inflammatory process in periapical tissues of rats with endodontic infection.…”
Section: Continuationsupporting
confidence: 77%
See 2 more Smart Citations
“…Consequently, lesions in the periapical area were larger in diabetic rats compared to those in the control group. 26 Subsequently, other animal studies 6,[27][28][29][30][31] comparing the severity of inflammation and periapical bone loss between patients with diabetes and normoglycemic controls were conducted and are in agreement with the findings obtained by Kohsaka et al 26 In addition, one of these studies showed that diabetes may enhance the production of IL-17 in the AP site of rats, 31 confirming that diabetes may influence the inflammatory process in periapical tissues of rats with endodontic infection.…”
Section: Continuationsupporting
confidence: 77%
“…There are multiple studies identifying AP as a factor that can potentiate the symptoms caused by inflammatory diseases such as diabetes. 6,[17][18][19] However, there is limited evidence in the literature showing AP as the primary cause of systemic disorders. Studies in humans and animals have been conducted in order to determine systemic molecular changes in the body of individuals with no systemic disorders, but with AP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another animal study (Prieto et al . ), it was found that, apical periodontitis did not alter the oxidative stress parameters in blood. Another study demonstrated that increased root canal endotoxin levels were associated with increased oxidative stress, severity of depression, and a lowered quality of life (Gomes et al .…”
Section: Discussionmentioning
confidence: 86%
“…In a pioneer study, conducted by Inchingolo et al (2014), it was reported that patients with chronic apical periodontitis exhibited significantly higher blood levels of oxidative stress than control patients and they suggested that subjects affected by chronic apical periodontitis are exposed to a condition of oxidative stress, which can be dangerous to general health. In another animal study (Prieto et al 2017), it was found that, apical periodontitis did not alter the oxidative stress parameters in blood. Another study demonstrated that increased root canal endotoxin levels were associated with increased oxidative stress, severity of depression, and a lowered quality of life .…”
Section: Discussionmentioning
confidence: 89%